Digital Leadership Synergy in Realizing Sustainable and Child-Friendly Education in the Era of Digital Transformation - Gaffar, Muhammad Andriana; Juwarto; Haryono, Wasis; Shofiyullah (Journal of Educational Management Research, 2025)
This study explores the synergy among digital Leadership, adaptive educational management, and data-driven planning to create a sustainable, child-friendly education system at SMAN 112 Jakarta. The transition to a digital education ecosystem in Indonesia faces challenges, including digital literacy gaps, infrastructure disparities, and resistance to change. The study aims to examine how these three elements can work together to improve educational outcomes and student Well-being. Using a qualitative approach with phenomenological case study methods, data were collected through in-depth interviews, participatory observation, and document analysis. The findings show that integrating digital Leadership, adaptive management, and data-driven planning has created an educational environment that is responsive to change and focused on the holistic development of students. The principal's Leadership has been key in driving digital transformation, while adaptive management has allowed the school to stay flexible in addressing challenges. This study contributes to the literature by providing insights into how schools can integrate technology, collaboration, and data to foster inclusive and resilient education systems.